PEMANFAATAN TUMBUHAN SEBAGAI BAHAN PENGOBATAN TRADISONAL OLEH MASYARAKAT DESA TELUK BATANG KECAMATAN TELUK BATANG KABUPATEN KAYONG UTARA - Rendiawati, Rendiawati; Oramahi, H A; Idham, M (Universitas Tanjungpura, 2019)
Utilization of plants as traditional medicine is a hereditary inheritance, which isobtained from ancestors until now is still preserved by the community. TheTeluk Batang of community, Teluk Batang District, North Kayong Regency also use medicinal plants as traditional medicine. This research aim at to document and describe the types of medicinal plants which are used for traditional medicine by the community of Teluk Batang Village, Teluk Batang District, North Kayong Regency. The method used in this research is to use survey methods with snowball sampling techniques, namely by conducting interviews with the community and the help of questionnaires. The results obtained from this study are in Teluk Batang Village, Teluk Batang District, Nort Kayong Regency that Â are 59 types of medicinal plants from 35 families were found to have medicinal properties. The most widely used plants of the Zingiberaceae family are 8 types of medicinal plants.Based on the most widely used habitus is herba whichis (40,6%) types of plants. The most used part of the plant is leaves, which are as many as (50,8%) species of plants. Based on the method of processing that is most often used is by boiling as many as (69,4%)species of plants. Based on the type of concoction the community uses a single concoction, while the most frequently used methods are taken by (64,4%) plants. Based on this plant cultivation, people have plants that are cultivated around home gardens and some that grow wild.Keywords: Traditional medicine,survey,processing of medicinal plants, Teluk Batang Villagge, Kayong Utara